2017
DOI: 10.1371/journal.pone.0181240
|View full text |Cite
|
Sign up to set email alerts
|

Emergent multisystemic Enterococcus infection threatens endangered Christmas Island reptile populations

Abstract: Multisystemic infections with a morphologically unusual bacterium were first observed in captive critically endangered Lister’s geckos (Lepidodactylus listeri) on Christmas Island in October 2014. Since then the infection was identified in another captive critically endangered lizard species, the blue-tailed skink (Cryptoblepharus egeriae) and two species of invasive geckos; the four clawed gecko (Gehyra mutilata) and Asian house gecko (Hemidactylus frenatus), in a wide geographic range across the east side of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…Examples of conservation breeding programs threatened by disease are those for the Christmas Island endemic Lister's geckos ( Lepidodactylus listeri ) and blue-tailed skinks ( Cryptoblepharus egeriae ) ( Rose et al., 2017 ). These species are extinct in the wild on Christmas Island, but are sustained in captive breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of conservation breeding programs threatened by disease are those for the Christmas Island endemic Lister's geckos ( Lepidodactylus listeri ) and blue-tailed skinks ( Cryptoblepharus egeriae ) ( Rose et al., 2017 ). These species are extinct in the wild on Christmas Island, but are sustained in captive breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…In reptiles, enterococci are known for their strong antimicrobial resistance (Prichula et al, 2016;Rose et al, 2017). The results of antimicrobial susceptibility tests performed in this study revealed that the E. faecalis isolate was resistant to 12 antibiotics (doxycycline, enrofloxacin, erythromycin, neomycin, oxytetracycline, gentamicin, amikacin, ciprofloxacin, spiramycin, chloramphenicol, ceftiofur, and azithromycin).…”
Section: Treatment and Discussionmentioning
confidence: 67%
“…A major disease threat emerged recently to the captive breeding program for two endemic Christmas Island reptile species. This invariably fatal disease was found to be due to infection with a previously unknown Enterococcus species, although the report documenting its occurrence did not formally describe it (Rose et al 2017). This unusual bacterium was recorded not only from individuals in the captive breeding program for threatened endemic lizards, but also in individuals of Christmas Island populations of introduced lizards (Rose et al 2017).…”
Section: Class Bacillimentioning
confidence: 99%
“…This invariably fatal disease was found to be due to infection with a previously unknown Enterococcus species, although the report documenting its occurrence did not formally describe it (Rose et al 2017). This unusual bacterium was recorded not only from individuals in the captive breeding program for threatened endemic lizards, but also in individuals of Christmas Island populations of introduced lizards (Rose et al 2017). Although the paper documenting its existence noted that there were no records of it from elsewhere, the current available information is insufficient to categorise it as native to Christmas Island, let alone endemic.…”
Section: Class Bacillimentioning
confidence: 99%